2013
DOI: 10.1242/dmm.013284
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of pathological small intestinal epithelial cell apoptosis and shedding induced by systemic administration of lipopolysaccharide

Abstract: SUMMARYThe gut barrier, composed of a single layer of intestinal epithelial cells (IECs) held together by tight junctions, prevents the entrance of harmful microorganisms, antigens and toxins from the gut lumen into the blood. Small intestinal homeostasis is normally maintained by the rate of shedding of senescent enterocytes from the villus tip exactly matching the rate of generation of new cells in the crypt. However, in various localized and systemic inflammatory conditions, intestinal homeostasis can be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
175
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(190 citation statements)
references
References 44 publications
13
175
1
1
Order By: Relevance
“…20 In addition, TLR4/NF-κB signaling pathway is also considered to be a major signal transduction pathway involved in apoptosis. 21,[26][27] It has been found that LPS caused IEC apoptosis through a TLR4-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, TLR4/NF-κB signaling pathway is also considered to be a major signal transduction pathway involved in apoptosis. 21,[26][27] It has been found that LPS caused IEC apoptosis through a TLR4-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Increased IP models are well established in humans (Ni et al, 2015;Piton et al, 2015), pigs , rats and mice (Williams et al, 2013;Ruan et al, 2014). Dextran sodium sulphate (DSS) ingestion, fasting (Kuttappan et al, 2015;Vicuna et al, 2015b), dexamethasone (Vicuna et al, 2015a) and wire floor stress (Wideman et al, 2012) have recently been employed as models of increased IP in chickens.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been determined that the IP of different strains is affected differently by DSS ingestion (Perše and Cerar, 2012). Lipopolysaccharide, found in the outer coat of gram-negative bacteria (Tran, 2009), has been well established as a model to increase IP in mice (Williams et al, 2013), rats (Ruan et al, 2014) and pigs . Although LPS has been used to induce systemic inflammation in chickens (Hu et al, 2011;Tan et al, 2014), limited research has been conducted regarding its effect on IP as reviewed by Gilani et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Accelerated shedding, which can lead to infection and exacerbated immune responses (Hausmann, 2010;Knodler et al, 2010), is associated with inflammatory bowel diseases (IBD; Kiesslich et al, 2012;Liu et al, 2011) and endotoxemia (Assimakopoulos et al, 2012). This 'pathological' shedding can be induced by proinflammatory cytokines or lipopolysaccharide (Williams et al, 2013). However, little is known about regulation of constitutive physiological shedding, and especially about signals that repress it.…”
Section: Introductionmentioning
confidence: 99%